Prototype of Cartoon Concept Teaching Book Based on Contextual Approach to Train Students’ Reflective Abstraction Skills - Rahmawati, Helmi; Fadli, Saiful (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to produce a valid, practical, and effective cartoon concept teaching book based on a contextual approach for training students’ reflective abstraction skills. This research method usesd research and development with the 4-D model, namely define, design, develop, and disseminate. Instruments used in this study include a validation sheet for the teaching book using the cartoon concept based on a contextual approach, a student response questionnaire, and pretest and posttest assessments of students’ reflective abstraction skills. The descriptive-quantitative technique was used to analyze the research data. Data on product-developed validity and practicality were analyzed descriptively. In contrast, the product’s effectiveness was analyzed descriptively using the n-gain formula and quantitatively using pretest-posttest control group design. The results of the study indicated that (1) the validity of the teaching book using the cartoon concept based on a contextual approach was valid (3.43) and reliable (85.71), (2) the practicality of the teaching book was considered practical with an average of 65.96, categorized as excellent, (3) statistical test results showed that the teaching book using the cartoon concept based on a contextual approach had a significant effect (sig. 2-tailed < 0.05) on students’ reflective abstraction abilities. The average improvement in pretest and posttest reflective abstraction skills was indicated by the N-Gain value in the experimental group (0.58 - moderate) and the control group (0.25 - low). Students in the control class performed reflective abstraction up to the process stage, while students in the experimental class engaged in reflective abstraction up to the object stage. Thus, the teaching book using the cartoon concept based on a contextual approach is valid, practical, and effective in training students’ reflective abstraction skills.